Supervised, structured and individualized exercise in metastatic breast cancer: a randomized controlled trial - Hiensch, Anouk; Depenbusch, Johanna; Schmidt, Martina; Monninkhof, Evelyn M.; Pelaez, Mireia; Clauss, Dorothea; Gunasekara, Nadira; Zimmer, Philipp; Belloso, Jon; Trevaskis, Mark; Rundqvist, Helene; Wiskemann, Joachim; et al. (Nature medicine, 2024)
Abstract - - Physical exercise both during and after curative cancer treatment has been shown to reduce side effects. Evidence in the metastatic cancer setting is scarce, and interventions that improve health-related quality of life (HRQOL) are much needed for patients with metastatic breast cancer (MBC). The multinational randomized controlled PREFERABLE-EFFECT trial assessed the effects of exercise on fatigue and HRQOL in patients with MBC. In total, 357 patients with MBC and a life expectancy of ≥6 months but without unstable bone metastases were recruited at eight study centers across five European countries and Australia. Participants were randomly assigned (1:1) to usual care (control group, - n -  = 179) or a 9-month supervised exercise program (exercise group, - n -  = 178). Intervention effects on physical fatigue (European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire (QLQ)-FA12 scale) and HRQOL (EORTC QLQ-C30 summary score) were determined by comparing the change from baseline to 3, 6 (primary timepoint) and 9 months between groups using mixed models for repeated measures, adjusted for baseline values of the outcome, line of treatment (first or second versus third or higher) and study center. Exercise resulted in significant positive effects on both primary outcomes. Physical fatigue was significantly lower (−5.3 (95% confidence interval (CI), −10.0 to −0.6), Bonferroni-Holm-adjusted - P -  = 0.027; Cohen's effect size, 0.22) and HRQOL significantly higher (4.8 (95% CI, 2.2-7.4), Bonferroni-Holm-adjusted - P -  = 0.0003; effect size, 0.33) in the exercise group than in the control group at 6 months. Two serious adverse events occurred (that is, fractures), but both were not related to bone metastases. These results demonstrate that supervised exercise has positive effects on physical fatigue and HRQOL in patients with MBC and should be recommended as part of supportive care. - - - ClinicalTrials.gov Identifier: - NCT04120298 - .
Gesehen am 31.03.2025